The Influence Of Compensation And Organizational Culture On PT Employee Performance. YamahaThamrin Brothers Manna-Kaur - Subandrio; Jorghi Mafrino (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This research aims to determine the influence of compensation and organizational culture on employee performance at PT. Yamaha Thamrin Brothers Manna-Kaur. This type of research uses quantitative descriptive research methods. The population used in this research were employees from PT. Yamaha Thamrin Brothers Manna-Kaur. The number of respondents in this study was 50 people. The data collection method uses a questionnaire and uses analysis techniques using multiple linear regression analysis tests and hypothesis testing, namely the t test and f test. Based on the results of multiple linear regression, the regression equation form Y = 2.224 + 0.531 X1 + 0.497 (2.192> 1.677) and (sig α = 0.001 < 0.005). This means H_0 is rejected and H_a is accepted. Organizational culture has a positive and significant effect on employee performance, this is proven by the results of the t test showing the value of tcount > ttable (2.097 > 1.677) and (sig α = 0.001 < 0.005). This means H_0 is rejected and H_a is accepted. Compensation (X1) and Organizational Culture (X2) together have a significant effect on Employee Performance (Y) at PT. Yamaha Thamrin Brothers Manna- Kaur, this is proven by the F test showing the value of fcount > ftable, namely 11.254 > 3.19 and (sig α = 0.000 < 0.005). This means H_0 is rejected and H_a is accepted.